Hermeneutika Khaled Abou El Fadl: Analisis dan Kritik Tipologi Islam Moderat dan Islam Puritan - Baihaqi, Nurun Nisaa (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
There was a discourse in analyzing the typology offered by Khaled Abou El Fadl to two groups of Muslims, namely the modern Islamic group and the puritan Islamic group. This is important considering that these two terms have been adopted and used as a barometer to distinguish the two groups. This research focuses on library research with the descriptive-qualitative method. That is by collecting research sources in the form of Khaled Abou El Fadl's writings and other reviewers who discuss and criticize their opinions. Then it is analyzed and described below, including the analysis of the author's personal opinion. From the results of the study, it can be seen that the hermeneutic theory offered by Abou El Fadl is closely related to the typology he proposed (moderate and puritan). The typology is more appropriate to be juxtaposed with the adherents or the person, not the religion or its teachings, namely Islam because it will narrow the meaning of Islam.